If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x * x) + 5x + -8x + 3(x * x) + 6x + -4 = 0 Multiply x * x 4(x2) + 5x + -8x + 3(x * x) + 6x + -4 = 0 Multiply x * x 4x2 + 5x + -8x + 3(x2) + 6x + -4 = 0 Reorder the terms: -4 + 5x + -8x + 6x + 4x2 + 3x2 = 0 Combine like terms: 5x + -8x = -3x -4 + -3x + 6x + 4x2 + 3x2 = 0 Combine like terms: -3x + 6x = 3x -4 + 3x + 4x2 + 3x2 = 0 Combine like terms: 4x2 + 3x2 = 7x2 -4 + 3x + 7x2 = 0 Solving -4 + 3x + 7x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -1x)(4 + -7x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(4 + -7x)' equal to zero and attempt to solve: Simplifying 4 + -7x = 0 Solving 4 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = 0 + -4 -7x = 0 + -4 Combine like terms: 0 + -4 = -4 -7x = -4 Divide each side by '-7'. x = 0.5714285714 Simplifying x = 0.5714285714Solution
x = {-1, 0.5714285714}
| 12.15=ev | | 8(x+4)=0 | | 12.16=ev | | 12z^2-35z+25=0 | | 2x+x=11 | | 2x-1=90 | | b^2+5b+4=0 | | 8(x+4)= | | N^2+n=30 | | 8(x+28)=8 | | 1/4(3x+1)=2(2x-4)-8 | | 8x^2-5=11 | | 3(2-c)-12=-3c | | 0.3x-0.2(3-5x)=-0.5(x-6) | | -18-2x=2-8x | | x+3x+2=14 | | c=10n+26 | | r+16=15r-10 | | 10n+26=54 | | n^2-16n+36= | | w^2-26=0 | | 6y-1-4y=17 | | x/4+2=7 | | -69-2(7)(-7)= | | 3(5x-4)-6(5x-7)=0 | | 4-10x=-5 | | 2(9s+10)-3s=3(5s+2)-10 | | 234234X+234234X= | | 2.4+0.4x=0.25(6+x) | | 6(x+5)=3(2x+4)+18 | | .8(x+40)+.2x=57 | | 24x+5x+67=24 |